Analisis Kesenjangan (Research Gap) Tren Publikasi dan Topik Materi Riset Etnomatematika di Indonesia: Studi Systematic Literature Review - Arju Nabihal Fikri; Nabilatun Nazihah; Jazilatul Hasanah; Shovi Azizy (PT Cendekia Education Center, 2026)
This study aims to identify research gaps in ethnomathematics publications in Indonesia regarding annual trends, geographical distribution, school levels, and mathematical topics. The method used is a Systematic Literature Review (SLR) with a qualitative-descriptive approach using content analysis techniques on 10 accredited articles published over the last five years. The results reveal a strong publication bias: the material focus is heavily dominated by geometry (>65%), the cultural locus is saturated within Java Island, and most studies are implemented at the elementary school (SD) level. Conversely, non-geometric topics and Eastern Indonesian cultures remain under-explored. In conclusion, ethnomathematics research in Indonesia suffers from imbalances in theme and regional distribution. Consequently, future researchers need to diversify mathematical topics and expand cultural exploration outside Java to support the equitable implementation of the Independent Curriculum.